The Evidence on Police Contributions to Crime Reduction: What Do We Know and What Does the Ottawa Police Service Do About It? - Norton, Adam P. (Université d'Ottawa / University of Ottawa, 2013)
There are two main objectives of this thesis. First, to review the social science evidence on the extent to which different police practices have been proven to reduce crime, or not reduce crime, as well as those cases where the evidence is not clear. This thesis synthesizes crime reduction strategies to short-list those practices that are proven to reduce crime. Second, it uses the evidence collected to facilitate an exploratory case study with three key informants from the Ottawa Police Service (OPS). The case study examines the current use and perceived future role of the police in evidence-based crime prevention efforts. Overall, the research study seeks to answer the following four research questions: 1. What sources of literature provide well-researched and reliable data on effectiveness of policing in crime reduction? 2. In this literature, what policing strategies/practices are shown to reduce crime, not reduce crime or are promising in reducing crime? 3. To what extent is the OPS using evidence-based knowledge to guide their policing strategy/practices? 4. To what extent is the OPS open to using evidence-based knowledge to guide their policing strategy/practices in the future?
Keywords: Crime prevention; Policing; Evidence based